Management Of Cardiogenic Shock In Pediatric Patients - Dyahris Koentartiwi; Naura A Candini; Renny Suwarnianty; Yunita L Indrianto (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2020)
Cardiogenic shock is an acute state of end-organ hypoperfusion following cardiac failure. Usually many children have good compensation if they suffered from cardiogenic shock and sometimes delay diagnosis leads to unfavorable outcome. Comprehensive approach in treatment following investigation about the cause of cardiogenic shock is very important and proper management will prevent complication and mortality.